(untitled) (مجلة إحالات, 2026)
This work aims to study the Quranic Term to Emir, Poet ,and the Sufis Abdul Qadir Al-Jazairi in his book “Al Mawakif in Preaching and Guidance” which is considered a comprehensive Quranic dictionary. He mentioned many Quranic Term in various fields; devotions, stories, behavior…It was in addition to the Sufi terminology present in the text of this mystical Sufi clue book. The aim of the research was to clarify the Quranic Term that addressed Emir Abdul Qadir AlJazairi in his book Al-“the halts” .